The Dynamic Feature of Macrophage M1/M2 Imbalance Facilitates the Progression of Non-Traumatic Osteonecrosis of the Femoral Head - Tan, Zhen; Wang, Yan; Chen, Yingqi; Liu, Youwen; Ma, Maoxiao; Ma, Zetao; Wang, Chao; Zeng, Hui; Xue, Lixiang; Yue, Chen; Wang, Deli (Frontiers in Bioengineering and Biotechnology, 2022)
Non-traumatic osteonecrosis of the femoral head (NONFH) remains a common refractory disease with poorly understood pathogenesis. Macrophage M1/M2 imbalance and chronic inflammatory microenvironment have been suggested to be closely related to osteonecrosis. Here we describe direct visual evidence for the involvement of dynamic changes in macrophages and the chronic inflammatory microenvironment in human NONFH. Osteonecrosis induces inflammatory responses and macrophage enrichment in the reparative area, and the number of inflammatory cells and macrophages falls during progressive- to end-stage NONFH. Multiplex immunohistochemistry demonstrated that macrophage M1/M2 ratio increased from 3 to 10 during progressive- to end- stage. During the progressive-stage, new blood vessels formed in the reparative area, M2 macrophages accumulated in perivascular (M1/M2 ratio ~ 0.05), while M1 macrophages were enriched in avascular areas (M1/M2 ratio ~ 12). Furthermore, inflammatory cytokines were detected in synovial fluid and plasma using cytometric bead arrays. Interleukin (IL)-6 and IL-1β were persistently enriched in synovial fluid compared to plasma in patients with NONFH, and this difference was confirmed by immunohistochemistry staining. However, only IL-6 levels in plasma were higher in patients with progressive-stage NONFH than in osteoarthritis. Moreover, fibrosis tissues were observed in the necrotic area in progressive-stage and end-stage NONFH based on Sirius Red staining. Together, these findings indicate that macrophage M1/M2 imbalance facilitates the progression of NONFH, a chronic inflammatory disease characterized by chronic inflammation, osteonecrosis and tissue fibrosis in the local lesion. Inhibiting inflammation, promoting the resolution of inflammation, switching macrophages to an M2 phenotype, or inhibiting their adoption of an M1 phenotype may be useful therapeutic strategies against NONFH.